Measures to Improve Agricultural R&D Governance Efficiency and Expand Private Investment (Year 2 of 2) - 이명기 (농업RnD 거버넌스 효율성 및 민간 투자 활성화 방안(2의2차년도), 2016)
The Korean government has been continually increasing R&D investment to realize the creative economy and strengthen competitiveness in the agricultural sector. However, it has been reported that its economic outcomes in solving the practical problems and improving the competitiveness in the agricultural industry have not been significant due to unclear establishment of key investment plans in consideration of national and agricultural policies, inadequate convergence research among the ministries and agencies, inadequate field application and commercialization of developed technologies, and insufficient private investment. To overcome such shortcomings, we need the user-led, network-type agricultural technology innovation system (ATIS) that can lead to innovation through mutual cooperation of agricultural holdings with stakeholders beyond "R&D extension and dissemination commercialization," a linear model centered on suppliers such as R&D institutes. This study is intended to present the strategy and measures to improve the outcome of ATIS that encompasses the governance and private investment by presenting the concept and components of A TIS and analyzing the roles and innovative capability of private and public sectors and the factors to strengthen the outcome.